DAMPAK KEBIJAKAN MORATORIUM PEGAWAI NEGERI SIPIL TERHADAP PENEMPATAN PEGAWAI DI PEMERINTAH DAERAH DAERAH ISTIMEWA YOGYAKARTA - Ahmad Harimurti Nugroho; Nur Widiastuti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
One important issue in the management of civil servants are Moratorium Acceptance CPNS. Since the 2011-2014 and 2015-2019 reign of discretionary moratorium CPNS caused by various things, impact of the moratorium on the placement of employees in local government and polemics consequences and need for a solution and response strategies in the redistribution of personnel and employee planning.This research uses descriptive research method with qualitative approach gained popularity depth interviews with informants, observations and secondary data analysis. Impact, occurrence Lost Generation that cause within a certain time difficult to regenerate for their miss a link on the generation / period. The addition of the workload of employees as a result of shortage of supply of labor civil servants, retired employee were not replaced, Minus growth means if in compare between employees incoming and outgoing, more employees are out of personnel expenditure would be reduced. So that in the possible procure Non civil servants without violating the moratorium policy is still valid.